Perancangan Playbook Untuk Wanita Yang Mengalami Haid - Saskia Sefi Syahsanas; Ida Siti Herawati; Rina Nurfitri (LPPM STIKI Malang, 2019)
The development in childhood to adulthood is marked with the onset of puberty that occurred on a regular basis in every month. At the time of teenagers should be a some of changes to the emotions result by several factors such as adjustments to the environment and others. The teenagers are at the time of menstruation have mood swings, and I want to find an activity so that they can improve mood. These activities can be done through the media that's interesting is that the playbook. What kind of book is made for women, adolescents who are having periods in the form of the interactive has several interesting topics. Therefore, designers make the playbook, â€œLet's Play Togetherâ€ who have the contents of games, diaog pictures, instructions, and information about menstruation. To promote the playbook has several media supporters of stationery, packaging, calender period, paper bag, totebag, and x-banner.